Evaluation of Employee Performance at PS Press Rental Start-Up in Semarang Using AHP Method - Aryasatya Abdie Maheswara; Iwan Setiawan (Informatics Engineering Department of Halu Oleo University, 2025)
Employee performance evaluation is essential for maintaining service quality and operational efficiency, especially in the entertainment industry. However, conventional evaluation methods often suffer from subjectivity and inconsistency. This study aims to implement the Analytical Hierarchy Process (AHP) as a decision support method to enhance objectivity and accuracy in employee performance appraisal at PS Press Start Id Rental Semarang. The AHP approach structures performance evaluation into a hierarchy of criteria productivity, competence, attendance, and service and applies pairwise comparisons to assign weights to each. The study involved designing a web-based evaluation system incorporating the AHP method. Results show that the AHP method successfully minimized subjectivity by ensuring a consistency ratio below the accepted threshold of 0.1. Employee performance was quantified and ranked, with Employee C identified as the top performer. Compared to the previous manual method, evaluation accuracy improved by 18% and decision-making time was reduced by 25%. Employee performance scores ranged from 0.62 to 0.88, with Employee C ranked highest. The system delivered accurate, transparent, and data-driven results, enhancing HR decisions related to rewards, promotions, and development planning. This research confirms AHP’s effectiveness in employee evaluation and offers a scalable model for similar organizations. These traditional approaches often lacked standardized weighting, leading to inconsistent scores and subjective variations of up to ±15% between evaluators. With the AHP-based system, the consistency ratio was reduced to 0.06 well below the accepted 0.1 threshold ensuring higher reliability. The system provided accurate, transparent, and data-driven results, improving HR decision-making processes related to rewards, promotions, and development planning. This research confirms AHP’s effectiveness in employee evaluation and offers a scalable model for similar organizations.